Development of Students’ Conceptual Understanding through STEAM Project Integration in Thermochemistry - Yuli Rahmawati; Syauqi Faizka Ramadhani; Afrizal Afrizal; Mela Puspitasari; Alin Mardiah (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This study aims to develop students' conceptual understanding by integrating the Science, Technology, Engineering, Art, and Mathematics (STEAM) project in thermochemistry. The qualitative research was employed with interviews, reflective journals, observations, students’ worksheets, and conceptual understanding tests on 40 students in senior high school. The STEAM project was implemented through a project-based learning model to develop students' understanding of exothermic and endothermic, combustion reactions, and enthalpy concepts. The STEAM project being developed is a steamship using three fuels: methanol, ethanol, and palm oil. The results showed that the student's understanding of enthalpy calculation had developed. Otherwise, the concept of exothermic, endothermic, and combustion reaction, especially related to applying the concept in daily life, is still undeveloped. Thus, some of the students experienced misconceptions. Therefore, the integration of contextual learning such as STEAM needs to be continuously applied to provide students with opportunities to develop their conceptual understanding and application in daily life.